Dating of Obsidian Tools by Water Diffusion (SIMS-SS) with a Novel Software - Liritzis, I.; Ganetsos, T.; Laskaris, N. (HNPS Advances in Nuclear Physics, 2020)
Diffusion of environmental water into the surface of obsidian tools of archaeological origin is monitored by secondary ion mass spectrometry (SIMS), which provides a H+ concentration (C) versus hydration depth profile. The modeling of this diffusion process, as one-dimensional phenomena, is based on the idea that a saturated surface (SS) layer is encountered near the surface. A novel software program has been developed, using MATLAB, incorporating all numerical parameters for the dating of hydrated obsidians using the SIMS profile. This approach has been applied to several archaeological obsidians from the Aegean, Hungary, and Asia Minor and compared with samples from radiocarbon dated cultural phases where the agreement is excellent.